Case Report: From disordered eating to an eating disorder—a case study of an orienteering athlete with anorexia nervosa and the shortcomings of the multidisciplinary approach - Kovács, Réka Erika; Boros, Szilvia (Frontiers in Psychology, 2025)
This case study explores the transition from disordered eating (DE) to an eating disorder (ED) in a 23-year-old female orienteer. Despite her talent as an athlete, her eating habits and training practices led to significant health concerns. After following an ovo-lacto vegetarian diet for 3 years, she exhibited symptoms of DE, including low energy intake (1,200 kcal/day), low body weight (50.1 kg, BMI: 16.9), and amenorrhea. Her condition deteriorated over 2 years, resulting in a diagnosis of anorexia nervosa (AN) by February 2023. During the treatment process, the athlete utilized a multidisciplinary approach that included dietitians, psychologists, and physicians. Despite achieving some initial progress, including a slight increase in body weight and the return of menstruation in July 2022, her health declined after psychological consultations were halted, leading to a further decrease in body fat and persistent low serum iron levels. This case highlights the importance of continuous monitoring, timely intervention, and a coordinated multidisciplinary team in addressing DE and ED in athletes. It also highlights the significance of effective communication among healthcare professionals and the need for comprehensive treatment strategies that include psychological, nutritional, and medical support. This study highlights the significance of early detection, suitable intervention, and the prevention of long-term health complications, such as decreased bone density and cardiovascular issues, in athletes with DE and ED.